2023
DOI: 10.3390/pharmaceutics15020518
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Antimicrobial Resistance and the Hospital-Wide Diverse Use of Broad-Spectrum Antibiotics by the Antimicrobial Stewardship Program in Japan

Abstract: Increased antibiotic use and antibiotic homogeneity cause selective pressure. This study investigated the correlation between antibiotic diversity and antimicrobial resistance (AMR) in Gram-negative organisms. The days of therapy/100 patient-days (DOT) for four broad-spectrum antibiotic classes were evaluated for 2015–2022. The antibiotic heterogeneity index (AHI) for the equal use of four classes (25%) and the modified AHI for the equal use of three classes (30%), excluding fluoroquinolones (10%), were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The SAAR was developed by the CDC to provide a risk-adjusted benchmark of antibiotic use. Ueda et al [ 20 ] reported the SAAR of broad-spectrum antibiotics predominantly used for hospital-onset infections in a Japanese TCH. Between 2015 and 2022, the SAAR ranged from 1.10 to 1.82 in the ICU, from 0.50 to 1.03 in the department of respiratory medicine, and from 0.70 to 1.20 in the department of colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SAAR was developed by the CDC to provide a risk-adjusted benchmark of antibiotic use. Ueda et al [ 20 ] reported the SAAR of broad-spectrum antibiotics predominantly used for hospital-onset infections in a Japanese TCH. Between 2015 and 2022, the SAAR ranged from 1.10 to 1.82 in the ICU, from 0.50 to 1.03 in the department of respiratory medicine, and from 0.70 to 1.20 in the department of colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroquinolones were used only in 12.5% of patients with bacteremia caused by difficult-to-treat gram-negative bacilli treated with broad-spectrum antibiotics in a Japanese hospital [ 30 ]. Recently, Ueda et al [ 20 ] reported that the % DOT values obtained in a rigorous 7-year AS program were 34.8% for carbapenems, 32.1% for piperacillin/tazobactam, 24.3% for fourth-generation cephalosporins/ceftazidime/aztreonam, and 8.9% for intravenous fluoroquinolones. From these results, a modified AHI for achieving a % DOT of 10% for fluoroquinolones and 30% for each of the remaining three broad-spectrum antibiotic classes was proposed, and an increased modified AHI value resulted in lower antibiotic resistant rates for P .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations